(untitled) (Archaeologia Adriatica, 2025)
From the iconographic and functional point of view, pillars with protomes of Jupiter Ammon and Gorgon (Medusa) are the most interesting elements of sculptural decoration of the Forum of Roman-era Iader. Their architectural context has not been unambiguously clarified. Mate Suić, a distinguished researcher of the Forum in Zadar, at first thought that they were standing inside of the front balustrade of the Capitoline temple. Although that is exactly how they are presented today, several details of their modelling refute this theory. It is possible that Suić eventually became aware of them, since later he changed his mind, attributing the pillars to “the upper balustrade” of the Severan basilica. Stylistic, technological and iconographic details, however, do not support such a possibility, as they indicate that the pillars are significantly older. In some texts, Suić’s attribution to the basilica is accompanied by drawing documentation that coincidentally shows the pillars inside the gallery of the forum portico, and this is exactly the position in which the pillars from Pula, similar in form and decoration, are placed. The recent discovery of a well-preserved pluteus functioning as railing between the Zadar pillars enabled a more accurate projection of the length of these elements, and thus the distance at which the pillars originally stood. Based on new findings and recent literature, the paper examines the possibilities of architectural contextualization of the Zadar pillars, as well as other important issues related to the reconstruction of the portico of the Zadar’s Forum as the most likely candidate for their placement: the dimensions of the pillars, the height of the portico, the affiliation of the pillars from the ground floor and the matroneum of St. Donatus.